ANALISIS PRODUKTIVITAS TENAGA KERJA DENGAN METODE WORK SAMPLING PADA PROYEK REHABILITASI DAN RENOVASI LABORATORIUM IAIN AMBON - Yakob Latuihamallo Latuihamallo; Glen Boyke Rehatta; Willem Gaspersz (Journal Agregate, 2023)
Project development nowadays is increasing, but on the other hand, the need for available quality resources is limited. The resources in question are human resources, materials and equipment. One very important factor is labor. If the workforce used is less skilled or not optimal in their work, then the results of the work will be poor. The quality obtained is not good and the productivity is low. The IAIN Ambon Laboratory Rehabilitation and Renovation Project really requires a careful calculation of the productivity of the workforce, so that an appropriate work system and the number of workers needed can be determined so that it can produce products that meet expectations. The analytical method used is the work sampling method where the percentage is obtained from adding effective work to ¼ essential contributory work, then dividing the sum by the total observations. The research results obtained LUR values ​​based on time divided into 2 (two) parts, namely the morning session from 08.00-12.00 and then the afternoon session from 14.00-17.00. The following results were obtained: A). The cleaning work was obtained: (Morning Time) Value Labor Utilization Rate (LUR) (85.21%) effective (82%), essential contributory (11%) and ineffective (7%). (Afternoon time) Labor Utilization Rate (LUR) (82.36%), effective (79%), essential contributor (12%), ineffective (9%). B). The best jobs obtained are: (Morning Time) Labor Utilization Rate (LUR) (90.10%), effective (88%), essential contributory (7%) and ineffective (5%). (Day Time) Labor Utilization Rate (LUR), (86.81%), effective (84%), essential contributor (12%) and ineffective (4%). C). Foundry work obtained: (Morning Time) Labor Utilization Rate (LUR) (86.56), effective (85%), essential contributory (8%) and ineffective (8%). (Day Time) Labor Utilization Rate (LUR) values ​​(87.50%), effective (85%), essential contributory (10%) and ineffective at 5%. From the work sampling results of overall sloof work on sloof work, the following are obtained: Labor Utilization Value Rate (LUR) (86.64%) effective (84%), essential contributory (10%) and ineffective (6%).